VỀ QUY TRÌNH LỒNG GHÉP CÁC YẾU TỐ MÔI TRƯỜNG VÀ BIẾN ĐỔI KHÍ HẬU VÀO CÁC QUY HOẠCH, KẾ HOẠCH VÀ CHƯƠNG TRÌNH PHÁT TRIỂN - Học, Trương Quang (Nhà xuất bản Nông nghiệp, 2016)
Climate change, with its resultant phenomena global warming and rising sea levels, is seen as one of the biggest challenges for mankind during the 21st century. Vietnam is one of the countries set to experience the most severe impacts from climate change. Therefore, adaptation to and mitigation of climate change has now become a priority task, both in the long term and in the short term, for Viet Nam. Climate change is of central concern for sustainable development, impacting on all regions, areas and fields throughout the world. Thus, climate change adaptation must be addressed in an aligned national program/plan and in close cooperation with the global community so as to protect our common shelter - the Earth - on which the most valuable resource - human beings - are living. Based on analyzing results and experiences of previous programs/projects such as the Vietnam - Sweden Cooperation Programme on Strengthening Environmental Management and Land Administration (SEMLA), the Poverty and Environment Project at MONRE, and others, a procedure of 6 stages for mainstreaming environmental and climate change issues into development planning, plans, programs and projects has been proposed. The procedure generally is based on a new version of the MONRE/SEMLA General Technical Guidance on Strategic Environmental Assessments which includes the integration of climate change adaptation and mitigation into the Strategic Environmental Assessment (SEA) process.